2018
DOI: 10.21037/cdt.2018.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Non-cardiac comorbidities in adults with inherited and congenital heart disease: report from a single center experience of more than 800 consecutive patients

Abstract: Non-cardiac comorbidities are increasingly common in ACHD. The data revealed non-cardiac comorbidities as they were presented in the cohort of ACHD seen in a tertiary center. The study proves that ACHD with significant non-cardiac comorbidities need multidisciplinary care by medical organ specialists, aside the congenital cardiologist, with a deep knowledge about congenital heart defects, the special effects of the organ disease on the particular heart defect and, how the heart defect may affect the course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
2
36
2
3
Order By: Relevance
“…Furthermore, non-cardiac comorbidities play major roles in lifelong ACHD care, but until recently, their importance was clearly underestimated. Neidenbach et al found that, out of 821 ACHD, over 95% had relevant non-cardiac comorbidities [9]. This finding was supported by Singh et al, a large contemporary study of ACHD hospitalizations (n = 255,355) from the US National Inpatient Sample Database [10].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Furthermore, non-cardiac comorbidities play major roles in lifelong ACHD care, but until recently, their importance was clearly underestimated. Neidenbach et al found that, out of 821 ACHD, over 95% had relevant non-cardiac comorbidities [9]. This finding was supported by Singh et al, a large contemporary study of ACHD hospitalizations (n = 255,355) from the US National Inpatient Sample Database [10].…”
Section: Introductionmentioning
confidence: 90%
“…However, most CHD patients are not completely cured and require medical follow-up or even subsequent "redo-surgery" [3]. All CHD patients, regardless of severity or type, have a chronic heart condition requiring regular follow-up with CHD cardiologists mindful of potential residua, cardiac sequelae, and comorbidities that may seriously affect the patients' health [9][10][11][12]. The importance of these residual and secondary diseases and the pronounced lifelong need for medical follow-up is illustrated by the significant increase in hospital admissions of ACHD in recent years [13].…”
Section: Introductionmentioning
confidence: 99%
“…and more than 90% of them reach adulthood [1]. Yet, the majority of adults with congenital heart disease (ACHD) is chronically ill due to lifelong residua and sequelae of the underlying heart disease [2][3][4] [2,3,4]. However, medical restraints are not the adults' only source of suffering, a sequence of life-altering experiences, such as early trauma, numerous hospitalizations and continuous medical emergencies may seriously impact their mental health status.…”
Section: Introductionmentioning
confidence: 99%
“…In the near future, preventive medicine measures will be of paramount importance for the care of patients with congenital heart defects (CHD) (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%